Analysing observer preferences when presenting a product in a rendered scene: 2D vs. autostereoscopic 3D displays. Issue 8 (3rd August 2019) - Felip, Francisco; Mulet, Elena; Galán, Julia; Remolar, Inmaculada
ABSTRACT: This research compares the way the image of a product included within a rendered scene shown on an autostereoscopic 3D display is rated versus the same image shown in a 2D display. The purpose is to understand the observer's preferences and to determine the features that a composition should have to highlight the product and to make its presentation more attractive to observers, thereby helping designers and advertisers who use both displays to prepare images to make them more effective when visually presenting a product. The results show that observers like the images on autostereoscopic 3D displays slightly more than those presented by means of 2D displays. On both displays the product is perceived more quickly when it is larger than the other elements and is shown with greater chromatic contrast, but a composition is seen as more attractive when the chromatic relationship between all the elements is more harmonious.